PENGARUH INTERNET BANKING, KUALITAS LAYANAN, REPUTASI PRODUK, LOKASI, TERHADAP LOYALITAS NASABAH DENGAN INTERMEDIASI KEPUASAN NASABAH - NURSIANA, ADINOTO (D-III Keuangan dan Perbankan, 2015)
Customer loyalty is one of the important factor that affect the growth of the bank.Â This research examinedÂ the effect of internet banking, service quality, reputation, product, and location Â on customer loyalty with the intermediationÂ customer satisfaction. As analycal tool in this research is using software LISREL 8.80.Result fromÂ this research. first, internet banking has a negative and not significant impact on customer satisfaction and customer layalty,Â second, service quality, reputation, product, and locationÂ have a positif and significant impact on customer satistaction, but its have a negative and not significant impact on customer layalty, third, customer satisfaction has a negative and not significant impact on customer loyalty.Â So as to enhance customer loyalty, banks need to provide the best relationship between bankâs marketer and customer.